CLOUD COMPUTING TECHNOLOGIES AND BUSINESS OPPORTUNITIES - Peniarsih Peniarsih (JURNAL TEKNOLOGI INDUSTRI, 2012)
Cloud computing is computing as a way of providing service. Allows you to use   a variety of applications, platforms and infrastructure developed on the basis of usability (such as using electricity!) Via the internet. Not only pay on what you wear, Cloud Computing gallows your team to use self-service for IT and the best part is, you do not have to start from scratch. Microsoft's latest technologies can launch you into the Cloud The term cloud computing may sound difficult and complicated. However, in terms of services, cloud computing today is actually simple, simple, and touches of everyday life. Cloud Computing. The term is familiar to the sudden lately, especially in the information technology world. Just what is cloud computing ? Cloud computing is translated into a simple cloud computing is these of internet-based computer technology. In making the diagram to  explain the Internet, often used to represent the internet cloud the picture. Maybe that is the origin of the word cloud computing. Key works  :  cloud computing, Technology, Internet